The Genetic Pathways Underlying Immunotherapy in Dilated Cardiomyopathy - Kadhi, Ayat; Mohammed, Fathima; Nemer, Georges (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is a global public health threat affecting 26 million individuals worldwide with an estimated prevalence increase of 46% by 2030. One of the main causes of HF and sudden death in children and adult is Dilated Cardiomyopathy (DCM). DCM is characterized by dilation and systolic dysfunction of one or both ventricles. It has an underlying genetic basis or can develop subsequent to various etiologies that cause myocardium inflammation (secondary causes). The morbidity and mortality rates of DCM remains high despite recent advancement to manage the disease. New insights have been dedicated to better understand the pathogenesis of DCM in respect to genetic and inflammatory basis by linking the two entities together. This cognizance in the field of cardiology might have an innovative approach to manage DCM through targeted treatment directed to the causative etiology. The following review summarizes the genetical and inflammatory causes underlying DCM and the pathways of the novel precision-medicine-based immunomodulatory strategies to salvage and prevent the associated heart failure linked to the disease.